2021
DOI: 10.3389/fpsyt.2021.634976
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Family Socioeconomic Status and Peer Relationships: Mediating Roles of Self-Esteem and Perceived Stress

Abstract: This study explored the relationships between subjective family socioeconomic status (FSES), self-esteem, perceived stress, and perceived peer relationships among Chinese adolescents. A total of 1,353 adolescents (age range: 15–19 years) were asked to complete a questionnaire. Mediation analysis revealed that subjective FSES influenced perceived peer relationships in three ways: first, through the mediating effect of perceived stress; second, through the mediating effect of self-esteem; and third, through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Studies have revealed the use of ladder ranking to be more powerful for reflecting the relationship between SES and individual mental health than other traditional objective indicators ( 25 27 ). The MSSSS-YV has also shown great reliability in Chinese college students (Cronbach's alpha coefficient: 0.79) ( 28 ). In the current study, the Cronbach's alpha coefficient was 0.90.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed the use of ladder ranking to be more powerful for reflecting the relationship between SES and individual mental health than other traditional objective indicators ( 25 27 ). The MSSSS-YV has also shown great reliability in Chinese college students (Cronbach's alpha coefficient: 0.79) ( 28 ). In the current study, the Cronbach's alpha coefficient was 0.90.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, adolescents with low family SES are often unable to participate in group activities and may be isolated in school. Moreover, they have lower level of self‐esteem, are more sensitive to peer rejection, and tend to withdraw and reduce interpersonal intimacy after interpersonal conflict and show more behaviors that disrupt relationships (Bai et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beside family relationship, poor relationship with peers during adolescence was related to poor mental health and alcohol consumption in later life in our study. Lack of financial recourses and higher level of stress among families with working-class belong, might reduce selfesteem in the children and negatively affect the quality of their relationship with their peers [84]. Quality relationship with peers particularly during adolescence has been suggested as an important element for social and emotional growth of individuals.…”
Section: Discussionmentioning
confidence: 99%